2009
DOI: 10.1021/nn8008883
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-electronic Superlattices in Silicon Nanoribbons

Abstract: Significant new mechanical and electronic phenomena can arise in single-crystal semiconductors when their thickness reaches nanometer dimensions, where the two surfaces of the crystal are physically close enough to each other that what happens at one surface influences what happens at the other. We show experimentally that, in silicon nanomembranes, through-membrane elastic interactions cause the double-sided ordering of epitaxially grown nanostressors that locally and periodically highly strains the membrane,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 28 publications
3
84
0
Order By: Relevance
“…It can be seen that the wavelength becomes increasingly dependent on the substrate thickness as its thickness c decreases below 0 / 2f͑͒. Such a decrease in the QD spacing with decreasing substrate thickness has been observed by Ritz et al 2 for Ge QDs on 6 and 23 nm Si nanomembranes. …”
Section: ͑7͒supporting
confidence: 67%
See 2 more Smart Citations
“…It can be seen that the wavelength becomes increasingly dependent on the substrate thickness as its thickness c decreases below 0 / 2f͑͒. Such a decrease in the QD spacing with decreasing substrate thickness has been observed by Ritz et al 2 for Ge QDs on 6 and 23 nm Si nanomembranes. …”
Section: ͑7͒supporting
confidence: 67%
“…Recently, it has been shown that some control of the QD size and spacing can be achieved through varying the thickness of the substrate. 2,3 The energetics of the system are strongly affected when the thickness of the substrate is comparable with the QD length scale. For ultrathin substrates, such as nanomembranes, 2,4 significant stress relief can arise due to bending of the substrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After these bottom-side dots are formed they in turn create preferential regions for a new set of dots to nucleate on the top (above their edges) and the process repeats. In such a fashion the process leads to the correlated dot growth as observed in experiments of Ge or SiGe islands on Si membranes [43,44]. This phenomenon can in principle be exploited to create periodic strained nanostructures that in turn produce periodically modulated band gaps.…”
Section: Applicationsmentioning
confidence: 89%
“…This result occurs as the strained quantum dots partially relax by straining the substrate membrane and thinner membranes are easier to deform than thicker ones. Such mechanism has been proved to play an important role in engineering the self assembly of thin film nanostructures such as quantum dots [43].…”
Section: Applicationsmentioning
confidence: 99%